Hydrogen storage ability of hexagonal boron nitride - Kovalskii, Andrey M.; Manakhov, Anton M.; Afanasev, Pavel A.; Popov, Zakhar I.; Matveev, Andrei T.; Al-Qasim, Abdulaziz S. (Frontiers in Materials, 2024)
The development of hydrogen energy is capable of solving a number of important issues that modern society is facing, including global warming and various environmental impacts. Currently, there is an intensive search for natural sources of hydrogen as well as low-carbon techniques for mass production of hydrogen from natural gas, associated petroleum gas, and water. In parallel, efforts to develop technologies for the subsequent management of hydrogen are underway, and the creation of its safe and efficient storage is one of the highest priority goals. For the transportation and storage of hydrogen today, a number of solutions are offered, each of which has both positive and negative aspects. The boron nitride (BN) family of materials with high thermal and chemical stability, variability of morphologies, and flexibility of structure has been considered as a candidate for efficient hydrogen storage. This review offers to familiarize readers with the progress in the research and application of hexagonal boron nitride (h-BN), as well as BN-based materials in comparison with other materials, as promising hydrogen storage. Experimental and theoretical data obtained for different morphologies and internal structures were reviewed in relevance to the material`s sorption capacity with respect to hydrogen. Various approaches to improve the efficiency of hydrogen storage were analyzed, and the highest storage capabilities published were mentioned. Thus, BN-based materials are very promising as hydrogen storage, even for an automotive application, but the development of new mass production technologies should be carried out.